Gerakan Masyarakat Sehat: Sosialisasi Penggunaan Obat Yang Baik dan Benar - Indriani, Nurul; Kresnapati, I Nyoman Bagus Aji; Qomaliyah, Eka Nurul; Pratiwi, Baiq Yulia Hasni; Ramandha, Muhammad Eka Putra; Muchsin, Lalu Busyairi (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Self-medication activities are increasingly found in the community. Self-medication is the use of medicines without a prescription on their initiative. Thus, irrational treatment often occurs, and both the duration and dosage of treatment are inappropriate. Appropriate self-medication activities can be started with a healthy living community movement (GERMAS) in the form of socialization of proper drug use. This community service in the form of socializing the use of proper medicines coupled with health checks was carried out to the people of Bagik Polak Village, Labuapi District, West Lombok Regency. This service activity was carried out through direct socialization methods followed by interactive discussions. The implementation of this community service activity went smoothly. The community enthusiastically participated in socialization activities on drug use and a series of health checks.   The discussion session was carried out with a number of questions and answers about drugs, handling, storage, and duration and dosage of treatment.